PENERAPAN DATA MINING MENGGUNAKAN ALGORITMA DECISION TREE C4.5 UNTUK MEMPREDIKSI MAHASISWA DROP OUT DI UNIVERSITAS WIRARAJA - Iddrus, Iddrus; Sari, Dewi Wulan (Journal of Advanced Research in Informatics, 2023)
Education providers are required to be able to provide good educational services and quality education to each student. Service and quality of education are provided to ensure students succeed in their academics. However, academic failures still occur in some students at various existing universities. One example of academic failure that often occurs is Drop Out (DO). DO is a condition where students are unable to complete their studies during the study period that has been given. DO is a big loss for students and education providers. By utilizing data mining, students should be able to predict from the start who are likely to experience dropouts. Based on these problems, a study was conducted to predict the probability of students dropping out using the Decision Tree algorithm C4.5 model. The test results obtained in this study are accuracy.